BiasCorrector: Fast and accurate correction of all types of experimental biases in quantitative DNA methylation data derived by different technologies. Issue 5 (26th May 2021) - Kapsner, Lorenz A.; Zavgorodnij, Mikhail G.; Majorova, Svetlana P.; Hotz‐Wagenblatt, Agnes; Kolychev, Oleg V.; Lebedev, Igor N.; Hoheisel, Jörg D.; Hartmann, Arndt; Bauer, Andrea; Mate, Sebastian; Prokosch, Hans‐Ulrich; Haller, Florian; et al.
Abstract: Quantification of DNA methylation in neoplastic cells is crucial both from mechanistic and diagnostic perspectives. However, such measurements are prone to different experimental biases. Polymerase chain reaction (PCR) bias results in an unequal recovery of methylated and unmethylated alleles at the sample preparation step. Post‐PCR biases get introduced additionally by the readout processes. Correcting the biases is more practicable than optimising experimental conditions, as demonstrated previously. However, utilisation of our earlier developed algorithm strongly necessitates automation. Here, we present two R packages: rBiasCorrection, the core algorithms to correct biases; and BiasCorrector, its web‐based graphical user interface frontend. The software detects and analyses experimental biases in calibration DNA samples at a single base resolution by using cubic polynomial and hyperbolic regression. The correction coefficients from the best regression type are employed to compensate for the bias. Three common technologies—bisulphite pyrosequencing, next‐generation sequencing and oligonucleotide microarrays—were used to comprehensively test BiasCorrector. We demonstrate the accuracy of BiasCorrector's performance and reveal technology‐specific PCR‐ and post‐PCR biases. BiasCorrector effectively eliminates biases regardless of their nature, locus, the number of interrogated methylation sites and the detection method, thus representing a user‐friendly tool for producing accurate epigenetic results.